2019
DOI: 10.1186/s13046-019-1248-2
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal cancer-derived extracellular vesicles induce transformation of fibroblasts into colon carcinoma cells

Abstract: Background We reported that horizontal transfer of malignant traits to target cells is a potential pathway to explain cancer dissemination. Although these results were encouraging, they were never corroborated by data showing the molecular mechanisms responsible for the observed phenomenon. Methods In the present study, we exposed BRCA1 -KO fibroblasts to extracellular vesicles (EVs) isolated from a colon cancer cell line (HT29) and from sera … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 53 publications
2
52
0
Order By: Relevance
“…Cancer EVs have been reported to regulate cancer invasion and metastasis [ 52 , 55 , 56 , 57 , 58 , 59 ]. Furthermore, we have previously shown that cancer EVs carrying mutated DNA and RNA induced malignant transformation of Fibro-BKO [ 60 ]. We analyzed the transforming abilities of UM-EVs on Fibro-BKO cells: at the end of a 3-week exposure to culture medium without EVs (No-EVs), NCM-EVs or UM-EVs, Fibro-BKO cells were inoculated subcutaneously into NOD/SCID mice.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cancer EVs have been reported to regulate cancer invasion and metastasis [ 52 , 55 , 56 , 57 , 58 , 59 ]. Furthermore, we have previously shown that cancer EVs carrying mutated DNA and RNA induced malignant transformation of Fibro-BKO [ 60 ]. We analyzed the transforming abilities of UM-EVs on Fibro-BKO cells: at the end of a 3-week exposure to culture medium without EVs (No-EVs), NCM-EVs or UM-EVs, Fibro-BKO cells were inoculated subcutaneously into NOD/SCID mice.…”
Section: Resultsmentioning
confidence: 99%
“…It was already known that circulating EV levels increase with advancing stages of cancer, suggesting potential roles in cancer progression and invasion [ 72 ]. Furthermore, we previously reported that EVs from different malignancies carry oncogenic factors that trigger malignant transformation in target cells [ 60 ]. In the present study, we wanted to verify whether EVs isolated from UM cell lines would trigger malignant transformation of Fibro BKO.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the process of breast cancer metastasis-induction by miR-105 is due to this metastatic cancer cell-to-host cell or to nonmetastatic cancer cell crosstalk mediated by breast cancer cell miR-105-shedding EVs [11,33]. Recently, researchers were able to show evidence of in vivo horizontal transfer of malignant traits when they injected colorectal cancer cell-derived EVs into the bloodstream of NOD/SCID mice and found malignant transformation of distant cells [48].…”
Section: Article Highlightsmentioning
confidence: 99%
“…They contain various components, such as maternal cell–derived proteins, miRNAs and mRNAs, and participate in intercellular substance and information exchange. Studies have found that tumour‐derived EVs can directly act on a variety of stromal cells, affecting the host's TME status, leading to tumour immune escape and progression . For example, tumour EVs contain a variety of proteins and RNAs that promote tumours by promoting polarization of M2 macrophages .…”
Section: Introductionmentioning
confidence: 99%